The Influence Of The Work Environment On Employees' Job Satisfaction At Baby Mush And Nasi Tim Mas Pandu Jl. Work Sensitive, Cibeber, Cimahi City - Ina Marlina; Alwi Al Hadad (Jurnal Scientia, 2024)
Work environment is an aspect that can influence employee job satisfaction, a conducive work environment can increase employee effectiveness and comfort in carrying out their work. This research will discuss the relationship between the work environment and employee job satisfaction in terms of managerial support, relationships between co-workers as well as the work atmosphere and clarity of tasks at the Babi Porridge and Rice Team Mas Pandu. The research method used is qualitative with data collection techniques through direct observation and interviews with the respondents, namely the 8 employees of the Mas Pandu baby porridge and rice team. The data analysis carried out in this research used an interactive analysis method by going through 4 processes, namely, data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the managerial support that has been implemented in the Mas Pandu team's baby porridge and rice greatly influences the job satisfaction of its employees, as well as good relationships between co-workers and a positive work atmosphere and clarity in providing effective work instructions. significantly increases employee job satisfaction. In this way, employees feel satisfied with a comfortable work environment and are enthusiastic in carrying out their duties which increases work productivity, therefore every company must implement a positive work environment